(3CNHGQ GdhGaOGJ Ydi eYGhjI Hf CHj SajGfs - (3CHi GdhdjO GdYHGS Hf HcGQ GdVHis; (3CHj GdhdjO GdYHGS Hf HcGQ GdVHjs
(3ChdgG (B:s
(3CNHQfG GdbGVi CHh GdbGSe Ydi GHf GdeMSf GdJfhNi bQGAI Ydjg ai efRdg bGd CdN s
(3BNQgG (B:s
(3deG JVQH HGdSjha QDSge hVQH GdbQGQ fbjYI Je cJGH s
(3QhGjI GdbGSe GdJfhNi Yf CMeO GHf YHOGddg GdeQhRi Yf TjhNg Yfgs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B11 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs